Sign up ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I would like to know the solutions of the functional equation:

$$f(x+f(y))+f(y+f(x))=2f(f(x))f(f(y)), \forall x,y\in\mathbb{R}$$

where $f:\mathbb{R}\rightarrow\mathbb{R}$. I have already determined that $f\equiv 0$ is a solution, and I would not be surprised if it was the only solution, but I have been unsuccessful in both proving this and finding a counterexample. Letting $a=f(0)$, I know that any other solution must satisfy

  • $f(a)=1$
  • $f(f(x))=f(x+a)$ (and more generally $f^{n+1}(x)=f(x+na)$)
  • $f(x+f(x))=f(f(x))^2=f(x+a)^2$ (and hence $f(x+f(x))>0$)
  • $f(2a)=f(1)$ (and more generally $f((n+2)a)=f(na+1)=f^{n+1}(1)$)
  • $f(3a)=f(a+1)=f(1)^2$
  • $f(2f(x))=f(f(x+a)^2)$

However, I cannot see how to derive a reasonable description of another solution/a proof that such a solution is impossible from this information. I'd appreciate some help with this. Thanks!

share|cite|improve this question
$f(a) = 0$ is another possibility. – Andrew Salmon Feb 27 '13 at 7:11
If $f(a)=0$, then $f\equiv 0$, which is why I did not mention the possibility in my description of a non-zero solution. If $f(a)=0$, then $f(f(x))=-f(x+a)$. We must also have $f(a)=a^2=0$, so $a=0$. Then $f(f(x))=-f(x)$, so $f(f(f(x)))=-f(f(x))=f(x)=f(-f(x))$. For every $p$ in the image of $f$ or the negative of the image, we must have $f(p)=-p$. However, when we let both $x$ and $y$ in the original equation equal $p$, we get $p=0$, so the range of $f$ is just $\{0\}$ and $f\equiv 0$. – rayradjr Feb 27 '13 at 7:51
$f(x)=1 \, \forall x \in \mathbb{R}$ works – Ivan Loh Feb 27 '13 at 11:13

1 Answer 1

Partial answer when the function have a root. Assume that there is $x_0\in \mathbb{R}$ such that $f(x_0)=0$. Set $y=x:=x_0$ in functional equation; implies that $f(0)^2=0$ i.e., $f(0)=0$. Set $y:=0$, we get that $$f(f(x))=-f(x)$$ Set $x:=f(x)$ and $y:=f(y)$ and also with recent relation we get that $$f(f(x)-f(y))+f(f(y)-f(x))=2f(x)f(y)$$ now in last relation, set $y:=x$ and conclude that $$f(x)=0.$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.